The impacts of telecommuting in Dublin. (September 2016) - O'Keefe, Paul; Caulfield, Brian; Brazil, William; White, Peter
Abstract: Telecommuting has been perceived as an effective means of reducing commuter related trips, travel time and emissions. Previously, the lack of access to broadband Internet connection and teleconferencing software from home has acted as a barrier to telecommuting regularly or at all. However, with advances in information and communication technology in recent years telecommuting is becoming a viable option for employers and employees to undertake. This paper examines the current trends of full day and part day telecommuting in the Greater Dublin Area (GDA), and attempts to ascertain the most influential drivers and constraints related to telecommuting. The research presented estimates of the environmental benefits from individuals that telecommute. Finally, this paper seeks to determine the magnitude of carbon emissions savings from individuals adopting telecommuting and provides a social cost of carbon saving value. The survey results presented suggest that approximately 44% of the population of the GDA telecommute at least once a month. The findings also indicate that needing contact with colleagues is the most influential constraint to telecommuting, while greater flexibility and avoiding travelling in peak periods are the most important drivers in the propensity to telecommute. Finally, this study shows that there are substantial carbon reductions and social cost of carbon savings. Thus illustrating how telecommuting can be a viable and sustainable policy in the GDA or in other similar sized regions.